Pentingnya Pendidikan Karakter Dalam Islam: Menanamkan Nilai-Nilai Keislaman Pada Anak-Anak Zaman Now - Wasilah Wasilah; Faisal Faisal; Aida Imtihana (STIKes Ibnu Sina Ajibarang, 2023)
Character education for children is a necessity and crucial to instill in today's generation. This article is a literature review research type, aiming to describe the importance of character education in Islam by instilling Islamic values in children. Based on the results and discussions above about the Importance of Character Education in Islam: Instilling Islamic Values in Today's Children, it can be concluded that character education in Islam has significant significance. The Quran and Hadith have taught that the responsibility of providing education to children lies with parents, educational institutions, and society. In the context of the current development of science and the globalization trend, Islamic values become the foundation that must be instilled in students. With a strong foundation, students can avoid deviation and inappropriate behavior. Islamic character education aims to strengthen and implement moral values found in Islamic teachings, such as honesty, justice, compassion, and tolerance. Through character education, Islam encourages the prevention of negative behaviors such as dishonesty, violence, and other harmful behaviors that contradict Islamic principles. The importance of developing noble morals is emphasized, with character education helping individuals cultivate qualities such as patience, sincerity, and humility in line with Islamic teachings. Social responsibility towards society is also taught by Islam, and character education helps individuals understand and apply social responsibility according to Islamic teachings. In the context of Islamic character education, the process can be carried out with the approach of emulating the example of Prophet Muhammad SAW. Emulating his behavior and morals is considered crucial in shaping an Islamic character. Character education also helps individuals live in accordance with the purpose of Islamic life, seeking the pleasure of Allah SWT, involving understanding and implementing Islamic teachings in daily life.